Developing A Competency-Based Career Path For Technical Job Position In Special Vehicle Division Of PT. PINDAD (Persero) - Eniya, Fathimah Noor; Wisesa, Anggara (Journal of Business and Management, 2016)
Abstract. Special Vehicle Division of PT. XYZ is the division that provides the defense vehicle for both defense ministry and also for commercial. As the development of the defense industry, Special Vehicle Division of PT. XYZ must keep their performance high to stand in market competition. To improve their performance, Special Vehicle Division should be supported by competent people. In the recent years, Special Vehicle Division of PT. XYZ face a problem of the loss of technical competencies. The Human Resources Department of PT. XYZ identified that the loss of competency is caused by the un-updated system of Career Planning in PT. XYZ. Specifically, PT. XYZ does not have a clear career path for the employee. The absence of the clear career path has made the employee moved from one job position to another job position without considering the competency that they already have in the previous position and what competency that required by the new job position. This unclear career path directly impact to the production divisions of PT. XYZ since they required specific technical competency to run the production process well. This research aimed to develop a competency-based career path for technical job position in Special Vehicle Ddivision of PT. XYZ in order to maintain the competency in the division. The development of career path is derived from company’s vision, mission, values and objective, and also from the analysis of the competency that is needed in Special Vehicle Division. The research developed career path for 41 technical job position in Special Vehicle Division of PT. XYZ based on the competency required for each job position. Key words : Competency, Career Path, Career Planning